Does Feeding Tube Insertion and Its Timing Improve Survival? - Teno, Joan M.; Gozalo, Pedro L.; Mitchell, Susan L.; Kuo, Sylvia; Rhodes, Ramona L.; Bynum, Julie P. W.; Mor, Vincent (Journal of the American Geriatrics Society (JAGS), 2012)
Objectives To examine survival with and without a percutaneous endoscopic gastrostomy (PEG) feeding tube using rigorous methods to account for selection bias and to examine whether the timing of feeding tube insertion affected survival. Design Prospective cohort study. Setting All U.S. nursing homes (NHs). Participants Thirty‐six thousand four hundred ninety‐two NH residents with advanced cognitive impairment from dementia and new problems eating studied between 1999 and 2007. Measurements Survival after development of the need for eating assistance and feeding tube insertion. Results Of the 36,492 NH residents (88.4% white, mean age 84.9, 87.4% with one feeding tube risk factor), 1,957 (5.4%) had a feeding tube inserted within 1 year of developing eating problems. After multivariate analysis correcting for selection bias with propensity score weights, no difference was found in survival between the two groups (adjusted hazard ratio (AHR) = 1.03, 95% confidence interval (CI) = 0.94–1.13). In residents who were tube‐fed, the timing of PEG tube insertion relative to the onset of eating problems was not associated with survival after feeding tube insertion (AHR = 1.01, 95% CI = 0.86–1.20, persons with a PEG tube inserted within 1 month of developing an eating problem versus later (4 months) insertion). Conclusion Neither insertion of PEG tubes nor timing of insertion affect survival.